EVALUATION OF THE NUTRITIONAL STATUS OF PATIENTS WITH CHRONIC LIVER DISEASES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Improving the organization and increasing the efficiency of clinical nutrition in the complex management of patients with various diseases is one of the most important problems of modern medicine. Chronic hepatitis is one of the most prevalent illnesses among liver diseases. The social significance of chronic hepatitis is determined by the fact that they can progress to liver cirrhosis and hepatocellular carcinoma, which are characterized by a high level of disability and mortality. Very little attention has been paid to factors associated with nutritional status which are abnormal in a significant number of patients with chronic hepatitis. The purpose of the study was to study the actual nutrition of patients with chronic liver diseases, which is determined as a risk factor in the development of the disease.